Association Between Inflammatory Markers and Myocardial Fibrosis: The MESA. Issue 4 (October 2018) - Marques, Mateus D.; Nauffal, Victor; Ambale-Venkatesh, Bharath; Vasconcellos, Henrique D.; Wu, Colin; Bahrami, Hossein; Tracy, Russell P.; Cushman, Mary; Bluemke, David A.; Lima, João A.C.
Abstract : Inflammation promotes adverse ventricular remodeling. T1 mapping has been used to noninvasively assess interstitial myocardial fibrosis. We examined the association of baseline markers of systemic inflammation with interstitial myocardial fibrosis measured by extracellular volume fraction (ECV) and native T1 mapping at 10-year follow-up in the MESA (Multi-Ethnic Study of Atherosclerosis). Seven hundred seventy-two participants had complete baseline data and underwent cardiac magnetic resonance imaging. All analyses were stratified by sex. Multivariable linear regression models were constructed to assess the associations of baseline CRP (C-reactive protein), IL (interleukin)-6, and fibrinogen with native T1 time and ECV. Longer native T1 times and higher percentages of ECV represent increasing myocardial fibrosis. A 1-SD increment of log-transformed IL-6 levels was associated with 0.4% higher ECV in men (β=0.4; P =0.05). CRP and fibrinogen were not associated to ECV. A 1-SD increment in the log-transformed CRP levels was associated with 4.9 ms higher native T1 (β=4.9; P =0.03). In women, the inflammatory markers did not demonstrate association with native T1 nor ECV. Higher IL-6 and CRP levels are associated with increased interstitial myocardial fibrosis assessed by cardiac magnetic resonance in men. However, no inflammatory markers were associated to myocardial fibrosis in women. Abstract : Supplemental Digital Content is available in the text.